Epidemiological evidence for associations between variants in CHRNA genes and risk of lung cancer and chronic obstructive pulmonary disease - Yang, Lei; Yang, Zelin; Zuo, Chunjian; Lv, Xiaolong; Liu, Tianyu; Jia, Chenhao; Chen, Huanwen (Frontiers in Oncology, 2022)
Background Genetic studies have previously reported that single-nucleotide polymorphisms (SNPs) in CHRNA genes (such as CHRNA3, CHRNA4, CHRNA5, or CHRNA3-CHRNA5-CHRNB4 clusters) are linked to the risk of neoplastic and non-neoplastic diseases. However, these conclusions were controversial and no systematic research synopsis has been available. We aimed to synthesize current knowledge of variants in the CHRNA genes on the risk of diseases. Methods We systematically searched for publications using PubMed, Medline, and Web of Science on or before 25 August 2021. A total of 1,818 publications were identified, of which 29 were deemed eligible for inclusion that could be used to perform meta-analysis based on at least three data sources to assess whether the morbidity associated with neoplastic and non-neoplastic diseases can be attributed to SNPs in CHRNA genes. To further evaluate the authenticity of cumulative evidence proving significant associations, the present study covered the Venice criteria and false-positive report probability tests. Through the Encyclopedia of DNA Elements (ENCODE) project, we created functional annotations for strong associations. Results Meta-analyses were done for nine genetic variants with two diseases chronic obstructive pulmonary disease (COPD) and lung cancer (LC)that had at least three data sources. Interestingly, eight polymorphisms were significantly related to changes in the susceptibility COPD and LC (p < 0.05). Of these, strong evidence was assigned to six variants (28 significant associations): CHRNA3 rs1051730, CHRNA3 rs6495309, and CHRNA5 rs16969968 with COPD risk, and CHRNA3 rs1051730, CHRNA3 rs578776, CHRNA3 rs6495309, CHRNA3 rs938682, CHRNA5 rs16969968, and CHRNA5 rs588765 with LC risk; moderate evidence was assigned to five SNPs (12 total associations) with LC or COPD risk. Data from ENCODE and other public databases showed that SNPs with strong evidence may be located in presumptive functional regions. Conclusions Our study summarized comprehensive evidence showing that common mutations in CHRNA genes are strongly related to LC and COPD risk. The study also elucidated the vital function of CHRNA genes in genetic predispositions to human diseases.